AB0823 Biochemical Markers of Bone Metabolism, Osteoprotegerin Serum Levels and Bone Mineral Density in Psoriatic Patients and their Relations to Disease Activity. (10th June 2014) - Rashad, S.M.; Abozaid, H.; Abozaid, H.; Moneer, M.; Sobhy, A.
Abstract : Background: Psoriatic arthritis (PsA) may be at an increased risk of osteoporotis (OP), but its degree has not been well-defined. Inflammatory cytokines have been implicated as the mechanistic link between immune system and bone metabolism. Osteoprotegerin (OPG) represents an essential cytokine for osteoclast function (Hofbauer, et al., 2006). Objectives: To evaluate biochemical markers of bone metabolism in psoriatic arthritis (PsA) and test osteoprotegerin (OPG) serum level and find out its correlation with disease activity and severity of bone loss assessed by bone mineral density (BMD). Methods: Sixteen patients with PsA (12 men) were enrolled in the study, attended the out-patient clinic of Rheumatology Department at Assiut and Alazhar University Hospitals. Ten healthy age-matched volunteers were served as controls. Their age ranged (47.75±13.9) and duration of the disease was (14.0±6.72). Clinical data, biochemical markers of bone turnover, serum OPG and BMD of lumbar spine and femur were evaluated. All patients fulfilled the diagnostic criteria for PsA defined by CASPAR, 2005. Blood samples were taken in the morning after an overnight fasting period. ESR, CRP, creatinine, calcium, alkaline phosphatase (ALP), and bone-specific ALP (bone ALP) were measured. Also free D-pyridinoline (f-Dpyr), a biochemical marker of bone resorption was assayed for patients and controls. Serum OPG was determined. BMD was measured at the lumbar spine and right femoral neck by (DEXA). Results: PsA had higher biochemical markers of bone resorption and inflammatory activity. PsA had a significant increase in ALP (236.94±88.95) and bone ALP (25.65±7.87), but not serum or urinary calcium when compared with controls. Urinary excretion of f-Dpyr was significantly increased in PsA (14.94±4.22) and was correlated with inflammatory measures. ESR>30 mm/hour had significantly higher levels of f-Dpyr than those with ESR<30 mm/hour (P<0.024) and those with CRP >6mg/L than those with CRP <6mg/L (P<0.046). It was not positively correlated with age and duration of the disease. OPG was significantly lower in PsA compared to controls (1.84±1.15), (p<0.001) and was not positively correlated with age. BMD of the hip and femoral neck were significantly lower in PsA than controls. Osteopenia was present in women, while osteoporosis was more frequent in men. Conclusions: Bone loss in patients with PsA is associated with high biochemical markers of bone resorption with inflammatory activity, and low OPG serum levels. In PsA patients, no evidence of severe osteoporosis where elevated bone ALP suggests ongoing bone formation. References: Hofbauer LC, Schoppety M, Christz M, Teichmann J and Lange U (2006): Tumour necrosis factor-related apoptosis-inducing ligand and OPG serum levels in PsA, Rheumatology, Advance Access publication; 45:1218–1222. Taylor WJ, Helliwell PS, Gladman DD et al. (2005): A validation of current classification criteria for the diagnosis of PsA preliminary results of the CASPAR study. Ann Rheum Dis; 64(Suppl. III):107. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3358